Effects of physical exercise, LEGO, and Minecraft activities on anxiety in underserved children with autism: Study design and methodological strategies - Angelina Lo; Lea Ann Lowery; Karen Kuhlthau; Robert A. Parker; James Chan; Fadia Haddad; Shlomit Radom-Aizik; Jean-G. Gehricke (MethodsX, 2023)
Anxiety is a common comorbidity for individuals with ASD, and there is some preliminary data about the efficacy of physical exercise to alleviate anxiety. However, we are not aware of any studies that have compared the effects of a physical exercise program on anxiety in underserved children with ASD using a randomized controlled research design. This paper describes a method to evaluate and compare the efficacy of an 8-week physical exercise intervention with a sedentary play intervention to alleviate anxiety in young children with autism spectrum disorders (ASD) from underserved backgrounds. We assessed anxiety and its physical symptoms using the parent-rated Child Behavior Checklist DSM-5 anxiety (CBCL DSM-5) subscale, the child-rated Screen for Childhood Anxiety Related Emotional Disorder (SCARED), the parent-rated Child's Sleep Habits Questionnaire (CSHQ), and salivary cortisol. We also utilized the Physical Activity Questionnaire for Older Children (PAQ-C) to assess physical activity level and identify compounds. Unique components of this study include: • Implementation of novel physical exercise and sedentary play interventions that have been designed for children with ASD. • Recruitment of predominantly underserved and non-English speaking families.